2020
DOI: 10.1016/s2468-2667(20)30140-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bystander-focused public health interventions on cardiopulmonary resuscitation and survival: a cohort study

Abstract: Background Bystander cardiopulmonary resuscitation (CPR) increases an individual's chance of survival from out-of-hospital cardiac arrest (OHCA), but the frequency of bystander CPR is low in many communities. We aimed to assess the cumulative effect of CPR-targeted public health interventions in Singapore, which were incrementally introduced between 2012 and 2016. Methods We did a secondary analysis of a prospective cohort study of adult, non-traumatic OHCAs, through the Singapore registry. National interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 35 publications
(36 reference statements)
0
42
1
1
Order By: Relevance
“…The incidence of OHCA has been rising every year, with crude incidence of 26.5 pmp in 2011 to 44.6 per 1000 pmp in 2016. While an increasing proportion of these survived (19.9% survived to admission, 6.5% survived to discharge in 2016) [ 26 ], a large majority did not survive to admission. All of Singapore’s 18 hospitals (8 public, 10 private) provide deceased donors for solid organ transplantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of OHCA has been rising every year, with crude incidence of 26.5 pmp in 2011 to 44.6 per 1000 pmp in 2016. While an increasing proportion of these survived (19.9% survived to admission, 6.5% survived to discharge in 2016) [ 26 ], a large majority did not survive to admission. All of Singapore’s 18 hospitals (8 public, 10 private) provide deceased donors for solid organ transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…Improvements in pre-hospital emergency care and bystander interventions have resulted in increasing proportions of out-of-hospital cardiac arrest (OHCA) cases with short no-flow or low-flow times (Pre-hospital/Emergency Department Return of Spontaneous Circulation (ED ROSC) rates at 18.3% in 2001–04 vs 23.8% in 2015–16) [ 24 26 ]. In the hospital setting, the progressive adoption of extracorporeal cardiopulmonary resuscitation (ECPR) characterized by the use of extracorporeal membrane oxygenation (ECMO) during CPR not only serves to optimize the outcomes of OHCA patients but may also become a bridging intervention towards uDCD for OHCAs who do not survive [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Таким чином, Audrey L Blewer та співавтори вказують на частоту позалікарняних серцево-легеневих реанімацій як важливу складову громадського здоров'я. Відповідно до даних Американської асоціації серця (American heart association (AHA)) cерцево-легенева реанімація (СЛР) не медичних працівників підвищує шанс людини вижити внаслідок зупинки серця поза лікарнею, однак частота таких СЛР у більшості країн низька (приблизно 40 %) [32].…”
Section: Assessment Of the State And Efficiency Of The Public Management And Administration Of The Communication Activity Of Public Healtunclassified
“…Bystander CPR rate is not a fixed feature of a region. It can be improved by interventions such as public information and training, as shown in a recent study from Asia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dispatch-assisted CPR has been implemented in many countries the last 20 years, and has in previous studies shown to improve the bystander CPR rates [ 7 ]. However major events in society may impact on bystander CPR.…”
Section: Introductionmentioning
confidence: 99%